UKM BERBASIS AGRIBISNIS UNTUK MEMBENTUK PENGEMBANGAN KETAHANAN PANGAN MASYARAKAT DI KABUPATEN OGAN KOMERING ULU - Eko mardiono; ema pusvita; purwadi purwadi (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2022)
The Small and medium Enterprise (SME) sector has a very important role in the economy of a country. Indonesia is one a developing countries that has a large business group,one of which is in the form os SMEs reached 8,568 spread across all sub-district in Ogan Komering Ulu district in January 2020 based on all SME fields but in of food sector the total number of SMEs onlu reached 3554 with different business sectors. In the food sector, there are 2109 micro-enterprise, 1363 small businesess and 82 medium-sized enterprise. The purpose this study is to analyze the typology and relationship of Agribusiness-based SMEs in shaping local food security in Ogan Komering Ulu Regency. Analyzing capabilities and strategies to create competitiveness in food SMEs in Ogan Komering Ulu Regency. This research was conducted in Ogan Komering Ulu Regency which is one of the regencies in South Sumatera Province. The location determination was carried out purposively with the consideration that Ogan Komering Ulu Regency is a Regency that has the potencial for rapid growth os SMEs so that it can maintain food security. The method used is a quantitative descriptive method and the data analysis method using the SWOT method. The data used comes from Ogan Komering Ulu district within a period of 10 years (2010-2020). The result of the reseacrh are issuing new innovations and knowing what is needed and what the community or producer want, socializing the important of growing food crops to support food security and introducing processed SME product made from food plants to the wider community, capital assistance from the government and pricing policy, estabilishing cooperation between SMEs in order to joinly advance agribusiness in the region.Keywords: SMEs, Agribusiness, Food Security.